Cost-effectiveness of two prevention cytomegalovirus infection schemes in renal transplant patients at intermediate risk in Colombia - Kateir Contreras; María José Vargas; Paola García; Camilo A. González; Patricia Rodríguez; Camilo Castañeda-Cardona; Margarita Otálora-Esteban; Diego Rosselli (Biomédica, 2018)
Introduction: Cytomegalovirus (CMV) is the most frequent opportunistic infection after renal transplantation. There are two strategies for its prevention: Universal prophylaxis, with valganciclovir for 90 days, and anticipated therapy, using weekly viral load surveillance, and therapy only if positive. Meta-analysis directly comparing both strategies have shown them to have similar effectiveness. Objective: To determine which strategy is more cost-effective in intermediate risk patients in Colombia. Materials and methods: We designed a third-party payer perspective decision tree, considering only direct medical costs in 2014 Colombian pesos (COP) (USD$ 1=COP$ 2,000) and a time horizon of one year. The target population was intermediate CMV risk patients (positive receptor). Transition probabilities were extracted from clinical studies, validated with a Delphi expert panel method; procedural costs were obtained from the ISS 2001 manual with a 33% increment based on the Consumer Price Index for 2014, while medication costs were obtained from the official Ministry of Health information system. Results: Universal prophylaxis with valganciclovir was dominant, with lower costs and less probability of infection. The average cost of the first year in anticipated therapy would be COP$ 30,961,290, whereas in the case of universal therapy the cost would be COP$ 29,967,834 (incremental cost of COP$ 993,456). Conclusions: For Colombian renal transplant patients at intermediate risk for CMV infection, universal prophylaxis strategy is the best option.